Proposed waqf crowdfunding models for small farmers and the required parameters for their application - Hassan Azganin; Salina Kassim; Auwal Adam Sa'ad (Islamic Economic Studies, 2021)
Purpose – Small farmers are considered one of the most affected communities worldwide due to poverty. Hence, this paper aims to study how the proposed waqf crowdfunding models are intended to provide alternative sources of funds for the waqf institutions and farmers. Design/methodology/approach – The present study employed a qualitative method by analysing the relevant literature on crowdfunding, waqf cash, waqf and agriculture, together with the primary sources of the Ḥadīth. Findings – This paper provides the conceptual framework of two waqf crowdfunding model (WCM) and the required parameters for their application. It is found that crowdfunding can bring immense benefits to the agriculture sector and farmers if it is integrated with waqf. This system will enable underprivileged farmers to meet their necessities and participate in their country's economic development. Research limitations/implications – Future research may consider a waqf crowdfunding integrated model targeting other businesses. Originality/value – This study provides the required parameters for the application of the proposed models. Four areas were analysed and discussed: the regulatory compliance parameters, the shariah compliance parameters, the risk management parameters and, finally, waqf governance parameters. To the best of the author's knowledge, this is the first proposed waqf and crowdfunding integrated model for agricultural financing.